Analisis Kinerja Keuangan Koperasi Pada KP-Ri Al-Amin SMAN 5 Tanjungpinang (Tahun 2021-2023) - R, Ratika; Sinaga, Rahel Garzia; Soimah, Nova Umi; Rikayana, Hadli Lidya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Savings and loan cooperatives are cooperatives whose activities are for the savings and loan business, the embodiment of savings cooperatives in managing the funds of their members, namely by maintaining the healthy performance of the cooperative because healthy performance is very important for a business institution. KP-RI Al-Amin SMAN 5 Tanjungpinang has never carried out an analysis using financial ratio analysis tools, so the level of efficiency of the funds being operational is not yet known. This research aims to determine the financial performance of KP-RI Al-Amin SMAN 5 Tanjungpinang in 2021-2023 using liquidity ratios, solvency ratios and profitability ratios. This research was conducted at the Republic of Indonesia Al-Amin SMAN 5 Tanjungpinang Employee Cooperative in May 2024. The object used in this research was an analysis of financial performance for the previous three years, namely 2021-2023 at KP-RI Al-Amin SMAN 5 Tanjungpinang. The research method used is a quantitative descriptive method. Data collection techniques are observation, interviews, documentation and literature study. The research results obtained on the liquidity ratio using the current ratio calculation got quite healthy results, while the solvency ratio analysis using the Total Asset to Debt ratio calculation got healthy results. The results of the profitability ratio analysis using Return On Equity calculations get unhealthy results. From the results above, it can be concluded that the financial performance analysis based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, Number 06/Per/M.KUKM/V/2006 is still not optimal. This is because there are still ratios that are within unhealthy criteria such as ROE.